Durability of Polymer Metal Multilayer: Focus on the Adhesive Chemical Degradation - Dubelley, Florence; Bas, Corine; Planes, Emilie; Pons, Emmanuelle; Yrieix, Bernard; Flandin, Lionel (Frontiers in Chemistry, 2018)
Mechanical toughness and high barriers to air and water may be combined in a polymer–metal multilayer film, provided that the two materials are properly bonded together. Delamination is indeed the most severe flaw observed in service. This suggests that the polyurethane (PU) adhesive at the polymer–metal interface fails to bear the shear forces, as happens principally if a multilayer system is submitted to elevated temperature and humidity. A Raman microscopy of the multilayer revealed a cohesive delamination, with glue on both the surfaces. A detailed investigation of the kinetic of degradation of the polyester was therefore carried out. IR spectroscopy of the standalone PU film hydrolyzed in a controlled manner furnished a series of aging markers. The reference curve was established for approximately a year in continuous severe aging conditions. This curve could be further used to compare the amount of degradation in real systems in a wide range of conditions and time. Moreover, at the metallized interphase, a complex with a free hydroxyl group was detected. The content of this AlIII complex based on terephthalate or carbamate increases with the progress of the ester hydrolysis reactionin the layer.